Kommunal-məişət və sosial obyektlərin elektrik enerjisi təminatının səmərəliliyinin artırılması üçün bərpa olunan enerji mənbələrinin tətbiqi - Qurbanov, Ayət; Məmmədli, Rəşid; Hacıyev, İsmayıl; Muradzadə, Murad (My University, 2024)
At the current stage of development, the cost of most technologies for energy production from renewable sources is 2-4 times higher compared to fossil fuel combustion technologies. However, considering ecological, social, and other factors, the comprehensive integration of renewable energy sources into the energy balance can be efficient. The system of mathematical models examined for renewable energy sources, which includes universal analytical models with variable parameters, allows for an accurate assessment of the complex potential of renewable energy sources.
Application of renewable energy sources to increase the efficiency of electricity supply to municipal and social facilities
Keywords: Renewable energy sources; Power Supply Problems